Digital Mapping of Dengue Mosquito Movement towards Weather Factors, Mosquito Density, and Cultural Factors in Jember Regency - Kukuh Jalu Prastyantoko; Dwi Wahyuni; Saiful Bukhori (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
This study aims to map a digital movement of the Aedes aegypti mosquito in high-risk areas for dengue fever outbreaks, taking into account the public's knowledge of dengue fever, attitude towards their environment, action towards the environment, environment conditions of the community, weather and climate factors, and mosquito density assessed through the House Index(HI). This study is a quantitative observational analytic research with a cross-sectional design. The result of the linear regression test on the cultural variable of knowledge, attitudes, and family support showed an value of α >0,05, indicating the knowledge, attitude, and family support are not important internal factors in aeradicating dengue fever. Mainwhile, the action and community leader support variable showed value α <0,05, which are important internal and external factors in reducing dengue fever levels. Then, HI value for these sub-districts is 6-7, meaning thet the mosquito density is high. The Aedes aegypti mosquito buffer zone has a flying distance 200 meters according to the CDC, so ares within that reach can be affected. This is clarified by using a digital map of the risk area of the Aedes aegypti mosquito causing dengue fever. In conclution, the digital map that includes cultural data, aera characteristics starting from weather, climate, population density, altitude, temperatue, humadity, and characteristics of mosquitoes inhabiting an area, whether they are clustered os spread, can cause the movement of dengue fever mosquitoes or Aedes aegypti to become more aggressive in their activities. So, the internal and external factors in the habitat of the Aedes aegypti mosquito can cause its movement to become more dunamic in spreading the dengue virus. Keywords: Aedes aegypti Mosquito, Culture, Dengue Fever, GIS (Geographic Information System)